KACAMATA SUNNI DAN SYI’AH DALAM MENAKAR NIKAH MUT’AH - M. Faizurrizqi Al-Farisi AD; M. Wildanul Ulum; Santi Ayuningtiyas (Comprehensive Journal of Islamic Studies, 2023)
The dynamics of the law of permissibility and the prohibition of mut'ah marriage among Muslims underwent serious discussion, this was spearheaded by two major groups, namely between the Sunnis (forbidding) and the Shia (allowing), each of which has a legal basis for arguments. strong. This study will focus on examining in terms of how mut'ah marriage according to these two groups and each legal basis used. As for the research method, this research uses library research with an approach to literature related to Sunni and Shia groups. So that the results are obtained in the form of a Sunni point of view that mut'ah marriage is prohibited because of the text by a new argument against the old one, while the Shiites deny this by giving an argument in the form of reasons and arguments. The urgency of this research is to provide clarity on the legal position which is still being debated by the two groups (Sunnis and Shi'ites) by reviewing the legal basis for each of them used for mut'ah marriages.